Peran Kepemimpinan Dalam Meningkatkan Motivasi Kerja Buruh Proyek Konstruksi Pada Proyek Pembangunan Perumahan Green Florencia PT. Megatopmas Prima di Kota Sidoarjo - Cahyono, Widi Dwi (Peneliti.net, 2024)
This study aims to determine the role of leadership in increasing work motivation and then to determine the constraints of leadership in increasing the work motivation of construction project workers in the Green Florencia housing development project PT. Megatopmas Prima in the city of Sidoarjo. The method used in this research is to use a qualitative descriptive research type with a case study approach, while the population in this study is a construction project worker leader, totaling 1 person and 6 construction project workers. The results of data collection in the field show that the role of leadership in increasing work motivation is that leaders ask workers to create various kinds of ideas once a week, always respect workers, provide inspiration for development, involve workers in making decisions, provide opportunities to lead, and provide achievement bonuses. The obstacles faced by leaders in increasing work motivation are that leaders find it difficult to determine the right tools to increase motivation, it is difficult to know the level of worker needs, weaknesses in anticipating the development of worker needs, and miscommunication often occurs.